A Glycine‐Targeted In Vivo Magnetic Resonance Spectroscopy for Quantifying Glycine in Glioma - Huang, Kai; Hao, Xiao‐Zhu; Fu, Cai‐Xia; Yang, Zhong; Ren, Yan; Yang, Xue; Zhang, Shi‐Ji; Zhu, Mei‐Lin; Yao, Zhen‐Wei; Wei, Da‐Xiu; Yao, Ye‐Feng (Journal of magnetic resonance imaging, 2025)
ABSTRACT Background Glycine (Gly) is a key metabolic intermediate in the proliferation of tumor cells. Monitoring the concentration of Gly in tumor tissues is of great importance for understanding the growth status of tumors. At present, magnetic resonance spectroscopy (MRS) is the only method to non‐invasively measure Gly concentration in human tissues. However, in conventional MR spectra the 1H signal of Gly overlaps with those of other molecules. This makes conventional MRS difficult to accurately measure the Gly concentration in human tissues. Purpose To develop a pulse sequence, Gly‐MRS, which can accurately measure Gly concentrations without the influence of the signal overlapping from other molecules in subjects with glioma. Study Type Prospective. Subjects/Phantoms A phantom of the glycine (Gly), myo‐inositol (MI) and glutamate (Glu) mixture aqueous solution and 6 phantoms of Gly aqueous solution (pH = 7.2 ± 0.1), 6 subjects with glioma (3 females and 3 males, BMI: 20 ± 4 kg/m2, age: 50 ± 10 years). Field Strength/Sequence 3 Tesla/A Gly‐targeted magnetic resonance spectroscopy pulse sequence, Gly‐MRS, using Point‐RESolved Spectroscopy (PRESS) for single voxel signal selection. Assessment By applying the developed pulse sequences to the phantoms and the subjects with glioma, the Gly 1H signals were successfully selectively probed. Quantification of the signals yields the concentrations of Gly in the regions of the tumor tissues of the subjects with glioma. Statistical Tests Numerical data only. Results The Gly 1H signals were detected in the tumor regions of 6 subjects with glioma, at a mean concentration of 5.20 mM (standard deviation, ± 3.29 mM). One subject exhibited a clear spatial distribution in the Gly concentrations in the tumor regions. Data Conclusion The Gly‐MRS pulse sequence developed in this work might be useful for the accurate in vivo detection of the 1H signal of Gly in gliomas of human beings. Evidence Level 2. Technical Efficacy Stage 3.